MRI Assessment of Ablation‐Induced Scarring in Atrial Fibrillation: Analysis from the DECAAF Study. (23rd April 2015) - AKOUM, NAZEM; WILBER, DAVID; HINDRICKS, GERHARD; JAIS, PIERRE; CATES, JOSH; MARCHLINSKI, FRANCIS; KHOLMOVSKI, EUGENE; BURGON, NATHAN; HU, NAN; MONT, LLUIS; DENEKE, THOMAS; DUYTSCHAEVER, MATTIAS; et al.
MRI Assessment of Ablation‐Induced Scarring in Atrial Fibrillation Background There is limited knowledge on the extent and location of scarring that results from catheter ablation and its role in suppressing atrial fibrillation (AF). We examined the effect of atrial fibrosis and ablation‐induced scarring on catheter ablation outcomes in AF. Methods We conducted a prospective multicenter study that enrolled 329 AF patients presenting for catheter ablation. Delayed enhancement magnetic resonance imaging (DE‐MRI) of the left atrium was obtained preablation. Scarring was evaluated in 177 patients with a DE‐MRI scan obtained 90 days postablation. We evaluated residual fibrosis, defined as preablation atrial fibrosis not covered by ablation scar. The primary outcome was freedom from recurrent atrial arrhythmia. Results In the analysis cohort of 177 patients, preablation fibrosis was 18.7 ± 8.7% of the atrial wall. Ablation aimed at pulmonary vein (PV) isolation was performed in 163 patients (92.1%). Ablation‐induced scar averaged 10.6 ± 4.4% of the atrial wall. Scarring completely encircled all 4 PVs only in 12 patients (7.3%). Residual fibrosis was calculated at 15.8 ± 8.0%. At 325 days follow‐up, 35% of patients experienced recurrent arrhythmia. Multivariable Cox proportional hazards models demonstrated that baseline atrial fibrosis (HR and 95% CIs) (1.09 [1.06–1.12], P < 0.001) and residual fibrosis (1.09 [1.05–1.13], P < 0.001) were associated with atrial arrhythmia recurrence, while PV encirclement and overall scar were not. Conclusions Catheter ablation of AF targeting PVs rarely achieves permanent encircling scar in the intended areas. Overall atrial fibrosis present at baseline and residual fibrosis uncovered by ablation scar are associated with recurrent arrhythmia.